Astronomy Magazine Fellowship - Rice, Jordan Noel (Proceedings of the Wisconsin Space Conference, 2017)
The Astronomy Magazine Fellowship, funded by the Wisconsin Space Grant Consortium, was an opportunity to work with Astronomy Magazine at Kalmbach Publishing in Waukesha, Wisconsin for 10 weeks in the summer of 2016 as the first student science writer.